PEMBENTUKAN KARAKTER SISWA SD : KOLABORASI ANTARA ORANGTUA, GURU, DAN TEMAN SEBAYA - Ma’ruf, Nadhifa Ginayu Hairina; Ratnaningrum, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Character development for elementary school students is a complex process that requires cooperation from peers, teachers and parents. With their love and guidance, parents act as the first line of defense in upholding moral and ethical principles in their children. Teachers encourage character development in the classroom by reinforcing these ideals through teaching strategies and daily example. Meanwhile, interactions with peers give children the opportunity to reinforce and teach social ideals such as tolerance, empathy, and collaboration. According to cognitive learning theory, students develop their moral character by internalizing the lessons they are taught and practicing them in various social situations. Collaboratively, parents, teachers and peers can ensure that values ​​are taught consistently, resulting in students who have high moral standards and strong character. Therefore, character development is a continuous collaborative effort to create a generation of people with high morals and integrity, not just the task of one party.